REAKSI INVESTOR TERHADAP PENGUMUMAN DIVIDEN DI BURSA EFEK INDONESIA - Sugeng Haryanto (Jurnal Keuangan dan Perbankan, 2011)
This study analyzed the investor reaction to dividend announcements. The sampling technique used waspurposive sampling with the criteria that these companies entered LQ45 2007-2009 and distributed cashdividends continuously. The purpose of this study was to investigate investor reaction to announcements ofcash dividends at Indonesia Stock Exchange. This research was an event study, the research analyzed themarket reaction to an event. This study aimed to test whether the information dividend announcement wasimportant information for investors and it affected investor reaction. Statistical analysis techniques were usedin different test against the Average Abnormal Return (AAR) before and after the dividend announcement. Theresults showed that investors did not react to that information. This was indicated by the absence of differencesin AAR before and after the dividend announcement.